DARI PENGALAMAN KE KESADARAN SOSIAL: IMPLEMENTASI EXPERIENTIAL LEARNING BERBASIS PROYEK DALAM PENGEMBANGAN KETERAMPILAN SOCIAL-EMOTIONAL MAHASISWA SEJARAH - Bonita Padang; Dyah Kumalasari (Jurnal Pendidikan Sejarah Indonesia, 2026)
This study aims to explore in depth how the implementation of Experiential Learning, which is realized through Project-Based Learning (PjBL), in Social History courses contributes to the development of students’ KSE. This study uses a qualitative case study Design. The research participants were students and lecturers from the History Education Study Program at the University of Riau, selected using purposive sampling. Primary data were collected through semi-structured in-depth interviews, which were then analyzed using hybrid thematic analysis. This analysis integrated a deductive theoretical framework (Kolb’s Model and CASEL Competencies) with inductive themes that emerged from the data. The main findings identify a systematic pedagogical mechanism. It was found that (1) Concrete Experience (field observation) serves as an emotional catalyst that triggers Social Awareness (empathy). (2) Reflective Observation (group discussions and class debates) becomes a crucial arena for practicing Self-Management and Relational Skills. (3) Abstract Conceptualization (connecting theory with practice) builds Self-Awareness and Decision Making. This process produces transformative impacts, including positive changes in perceptions of social activism and a significant increase in self-efficacy. The main supporting factor is the pedagogical design deliberately created by lecturers. In contrast, the main obstacle is structural: limited time available for lecturers to provide guidance due to conflicts with their administrative workload. This study concludes that Experiential Learning-based Social History learning has proven to be a highly effective model for developing students' social-emotional skills holistically. These findings imply that Experiential Learning in history education not only transfers knowledge but also successfully transforms students into more empathetic, critical, and socially courageous individuals, highlighting the importance of institutional support to protect reflective interaction time between lecturers and students.